Infant Mortality and Race in Kansas - Nikki Keene Woods; Jared Reyes; Amy Chesser (SAGE Publishing, 2016)
Background: Racial and ethnic minority infants and mothers have worse birth outcomes than Caucasian infants and mothers, specifically infant mortality. The purpose of this pilot study was to compare infant mortality rates from vital statistic data between mothers who participated in the Women, Infants, and Children (WIC) Program and the general population in Kansas. Methods: A retrospective secondary analysis of data received from the Kansas Department of Health and Environment (KDHE) was conducted. Data were provided on all mothers who delivered a child in the state of Kansas from 2009 to 2011. The data received from KDHE included maternal demographics, infant deaths, infant gestational age, infant weight at birth, and WIC program participation. Results: The overall infant mortality rate was 6.4 per 1000 births. Infant mortality for Caucasians was lower than for non-Caucasians. Infant mortality for blacks was greater than for non-blacks. Being Hispanic was not statistically associated with a difference in infant mortality. WIC program participation was associated with lower infant mortality in both blacks and Hispanics. After adjusting for WIC, infants born to black mothers were still more than twice as likely to die when compared with Caucasian infants. WIC services were not statistically associated with a reduction in infant mortality. Mother's education showed a significant protective effect on the likelihood of infant death. Conclusion: The WIC program is associated with positive outcomes at the national level. However, widespread reductions in health disparities have not been reported. Differences in education levels between mothers affected infant mortality to a greater degree than WIC program participation alone in the analysis. The infant mortality rate for black and Hispanic mothers was lower for WIC program participants. The WIC program may be beneficial for reducing infant mortality racial disparities but program participation should be expanded to affect maternal health disparities at the population level.